Предмет: Алгебра,
автор: dart75
Упростите выражение
Приложения:
Ответы
Автор ответа:
1
Ответ:
Объяснение:
(a⁴+a²-2)/(a³-a²+2a-2)=a+1.
Разложим на множители числитель:
a⁴+a²-2=0
Пусть а²=t ⇒
t²+t-2=0 D=9 √D=3
t₁=a²=1 t₂=a²=-2 ⇒
(a⁴+a²-2)=(a²-1)*(a²+2)=(a-1)*(a+1)*(a²+2)
Разложим на множители знаменатель:
a³-a²+2a-2=a²*(a-1)+2*(a-1)=(a-1)*(a²+2). ⇒
(a-1)*(a+1)*(a²+2)/((a-1)*(a²+2))=a+1.
Похожие вопросы
Предмет: Другие предметы,
автор: Аноним
Предмет: Математика,
автор: e2788783
Предмет: Алгебра,
автор: Bipolarh
Предмет: Литература,
автор: бабашка1
Предмет: Обществознание,
автор: kinder01997